Liturgical Renewal and the Formation of Faith: Nurturing a Resilient Spirituality in Millennials and Generation Z - Jusuf Hutapea (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2026)
The contemporary church faces a profound challenge in nurturing the spiritual lives of Millennials and Generation Z, as these generations demonstrate declining affiliation and participation in traditional religious institutions. While much scholarly attention has focused on pragmatic strategies to increase attendance and engagement among young congregants, this study argues that liturgical renewal must be understood primarily as a means of faith formation rather than merely as a tool for attracting young people. This research aims to analyze how liturgical renewal can be intentionally designed to nurture a resilient, deeply rooted spirituality that enables younger generations to navigate the complexities of a secular and digitally saturated world. Employing a qualitative case study approach, this research investigates churches that have implemented significant liturgical reforms, examining their impact on the spiritual growth, theological understanding, and long-term faith commitment of young congregants. Data were collected through participant observation, in-depth interviews with church leaders and young adults, and analysis of liturgical documents, and were analyzed thematically. The findings reveal that engagement-focused renewal without intentional formation produces superficial results, while formation-oriented liturgical practices integrating reflective spaces, intergenerational dialogue, creative expression, and digital media foster deep engagement with Christian tradition. Effective models of renewal prioritize the formation of spiritual habits, theological literacy, and a robust sense of belonging, equipping young believers to sustain their faith through transitions, doubts, and cultural pressures. This study contends that liturgical renewal, when approached theologically rather than pragmatically, serves as a vital strategy for cultivating resilient faith that can withstand the challenges of contemporary life. The research recommends a holistic approach to liturgical development that integrates formation-oriented practices, intentional catechesis, and ongoing evaluation to ensure alignment with the spiritual needs of younger generations.